Ex Vivo Human Placental Transfer of Rifampin and Rifabutin - Kevin P. Magee; David Wimberley; Caren Crane; Sohrab Sobhi; Roger E. Bawdon (Hindawi Limited, 1996)
Objective: The purpose of this study was to determine the ex vivo human placental transfer of rifampin and rifabutin.